Ion accelerator based on plasma vircator - Onishchenko, I.N.; Pushkarev, S.S. (Вопросы атомной науки и техники, 2001)
Based on previous fundamental and experimental research [1, 2] the conception of a collective ion accelerator is proposed to be developed in the frameworks of STCU project #1569 (NSC KIPT, Ukraine) in coordination with the ISTC project #1629 (VNIIEF, Russia). The main processes of acceleration are supposed to be consisted of two stages. First one is the plasma assistance virtual cathode (VC) in which plasma ions are accelerated in a potential well of VC. Along with ion acceleration the relaxation oscillations, caused by diminishing the potential well due to ion compensation, arise that provides the low-frequency (inverse ion transit time) temporal modulation of an intense relativistic electron beam (IREB) current. At the second stage temporally modulated IREB is injected into the spatially periodic magnetic field. The further ion acceleration is realized by the slow space charge wave that arises in IREB due to its simultaneous temporal and spatial modulation.